Smart Parcel Receiver - Phua , Zhi Heng; Mohd Ariffin, Nur Solehah; Yeo , Yong Jia; Tuan Ibrahim, Tuan Mohd Hafeez; Wagiman, Abdullah; Yahya, Mohd Shahir (Multidisciplinary Applied Research and Innovation, 2025)
The rise of e-commerce has increased package delivery. The increased frequency of delivery increases the potential for theft, particularly in residential areas where parcels are frequently left unattended. Theft of parcels in the context of online purchasing is a major worry for both customers and e-commerce businesses. The purpose of this research is to design, develop, and evaluate a Smart Parcel Receiver. The goal of this research is to assist recipients in keeping their parcels secure during delivery. This project has used five phases in the engineering design process to complete this paper. The engineering design phase includes formulation, concept design, configuration design, parametric design, and detail design. To use this machine sender needs to contact the receiver of the parcel so that the receiver can unlock the door of the machine remotely using an app. Overall, the project achieved the study’s goals. However, there is still room for development in product design and app usage.